INTEGRATED FAMILY:PASTORAL ASSISTANCE FOR BROKEN HOME TEENAGERS IN SION PACCERAKAN CHURCH - Gidion Tappi; Yansar Toban, Mariani Rombe Payung, Pores Asriel (CV. ADIBA AISHA AMIRA, 2022)
Broken Home children at Toraja Congregation Sion Paccerakan Church in Luwu Class. As a church assembly, they must fulfill their ministry duties properly, especially in carrying out pastoral assistance services. Pastoral assistance is very important so that the Broken Home child can rise from his life struggles. The author discusses this topic because pastoral assistance services for Broken Home children have not been optimally implemented. In connection with the topics raised in the completion of this writing, the authors use qualitative methods. The data collection technique used is through the literature and field research using the interview method. The author conducted research at the Congregation of Sion Paccerakan Klasis Luwu. The informants were the Pastor, Church Council, Guardian Parents and Broken Home Teenagers. Based on the results of research in the field, the authors found that broken home children understand their life as five things namely ugliness, destruction, freedom, solitude and pleasure. Responding to these findings, the church needs to help children in the form of pastoral assistance to find life goals